Pengaruh Latihan Aerobik Terhadap Peningkatan Volume Maksimal Oksigen (VO2 MAKS) Pada Perokok - Haraphap, Sunan Thariq Horas, Totok Budi Santoso , S.Fis , MPH, Sugiono S.Fis.MH.Kes (2015)
Background: The maximum volume of oxygen (VO2 max) is the oxygen uptake ability with a maximum capacity to be used by the body, if the oxygen uptake disturbed there will be a reduction in maximum oxygen volume, one reason is that there is carbon monoxide in rokok.Merokok can cause damage to the lining of blood vessels making it easy to build up, disturb heart rhythm Carbon Monoxide (CO), is one of the toxic gas that lowers the oxygen content in the blood. Nicotine content, gas CO, free radicals, and these substances can damage the endothelial lining of blood vessels. , If the form of a plaque in blood vessels, it can be a beginning of the process arteroklerosis which can cause a variety of cardiovascular diseases (Syaifuddin, 2011). So that the smoker is not only a risk of lung disorders but also a risk of disorders of the heart and blood vessels, this will result in a decline in cardiorespiratory performance will result in a reduction in physical fitness. Objective: To examine the effect of aerobic exercise to increase in Vo2 max in smokers. Pelnelitian Methods: This study used a study design quasieksperimental with pre and post test with control design.Populasi and Sample: The population in this study are members of the Islamic Student Association of the University of Muhammadiyah Surakarta of 20 people, 10 people treated group and 10 control group. Data Analysis: An analysis using the Wilcoxon testuntuk determine the effect of pre and post testpada treatment group or the control group. For different test post test between groups using the Mann-Whitney test. Results: Statistical test treatment groups at Wilcoxondidapatkan test p = 0.002 which means that there is an influence of aerobic exercise on aerobic exercise. On the Mann-Whitney test p value = 0,0eyang means that there are differences in the effect after the exercise in the treatment group and the control group. Keywords: Aerobic exercise, VO2 max, Smoker